Educational Impact of a Didactic Instrument That Complements the TADIR for Concepts of Statics in Engineering Students in Mexico - Federico Alonso Morales-García; Mario Humberto Ramírez-Díaz (Universidad Nacional, Costa Rica, 2016)
Observing in school structural designs reviews that students had little conceptual command of Statics, and considering that this was due to the implementation of linear solutions of rote-learning type, there was an effort to establish an educational proposal to raise the level of such knowledge among students. Therefore, the present study aimed to evaluate the educational impact achieved with the implementation of an educational instrument designed according to the sequence established in the TADIR protocol, and complemented with thoughtful activities to organize knowledge to prepare a presentation to the group. Three stages were considered for the implementation: the first one corresponds to the assessment of the level of conceptual knowledge in statics; the second one, a problem solving carried out with the proposed instrument; and the third stage focuses on the preparation of the presentation to the group, and closes with a second conceptual evaluation. The didactic instrument was applied in a group of 23 students from an intermediate level of Architect Engineer studies at the Superior School of Engineering and Architecture (ESIAT) of the National Polytechnic Institute (IPN) in Mexico. To measure the educational impact, the results were compared with the two conceptual evaluations conducted by using questionnaires that allow answers written within an established format to facilitate the codification and the corresponding analysis, and it was contrasted with school grades for better reference. The main finding was that although the increase in the conceptual command is greater than the school grading, this increase can be very important to improve the school approval rates.